The biosafety research road map: the search for evidence to support practices in the laboratory—Mpox/monkeypox virus - Blacksell, SD; Dhawan, S; Kusumoto, M; Le, KK; Summermatter, K; O'Keefe, J; Kozlovac, J; Al Muhairi, SS; Sendow, I; Scheel, CM; Ahumibe, A; Masuku, ZM; et al. (Mary Ann Liebert Inc., 2023)
Introduction: The virus formerly known as monkeypox virus, now called mpoxv, belongs to the Orthopoxvirus genus and can cause mpox disease through both animal-to-human and human-to-human transmission. The unexpected spread of mpoxv among humans has prompted the World Health Organization (WHO) to declare a Public Health Emergency of International Concern (PHEIC).